Keris Melayu Semenanjung : suatu pengenalan - Abdul Mua'ti @ Zamri Ahmad (Serdang, Selangor : Penerbit Universiti Putra Malaysia, 2015)
History of Keris, a traditional weapon in Malaysia.
Includes bibliographical references : page 130 and index.
In Malay.
Keywords: Daggers, Malay; Weapons -- Malaysia